2015
DOI: 10.1007/s00249-015-1014-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2-amino-8-hydroxyquinoline interaction on the conformation of physiological isomers of human serum albumin

Abstract: The methods of synthetic chemistry create small molecules rapidly for screening, and ligand-protein interaction studies provide information on how a potential drug interacts with target or carrier proteins such as serum albumin. In this work, we investigate the interaction of amino derivative of 8-hydroxyquinoline, 2-amino-8-hydroxyquinoline (A8HQ), and the effects of its binding on the conformation of different isomers of human serum albumin (HSA) using multispectroscopic techniques and molecular modeling. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, 8-hydroxyquinoline favors to be docked into a pocket at an interface between domains I and II of HSA by networking with Lys106, Gln29, Tyr148, Tyr150, and Cys246 [19]. The nitro [20] and the amino [21] derivatives of 8-hydroxyquinoline prefer to form complex with serum albumin by a moderate affinity at about 10 5 M −1 binding constant. Furthermore, derivative of cloxyquin bearing iodo group at the 7 th position (5-chloro-7-iodo-8-hydroxyquinoline or clioquinol) exhibits extreme affinity toward BSA with a binding constant of 10 8 M −1 [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, 8-hydroxyquinoline favors to be docked into a pocket at an interface between domains I and II of HSA by networking with Lys106, Gln29, Tyr148, Tyr150, and Cys246 [19]. The nitro [20] and the amino [21] derivatives of 8-hydroxyquinoline prefer to form complex with serum albumin by a moderate affinity at about 10 5 M −1 binding constant. Furthermore, derivative of cloxyquin bearing iodo group at the 7 th position (5-chloro-7-iodo-8-hydroxyquinoline or clioquinol) exhibits extreme affinity toward BSA with a binding constant of 10 8 M −1 [22].…”
Section: Introductionmentioning
confidence: 99%
“…5A8HQ possessed drug-likeness properties with high water solubility and intestinal absorptivity. Fluorescence quenching studies indicated that 5A8HQ was associated with BSA through the ground-state complex formation with a moderate binding constant at 10 4 M −1 , which was comparable to other 8HQ derivatives, such as 2‑amino‑8‑hydroxyquinoline 62 and 5-chloro-8-hydroxyquinoline 50 , but not clioquinol (5-chloro-7-iodo-8-hydroxyquinoline; = 10 8 M −1 ) 58 . However, in vitro obtained binding constant is a preliminary information, which may need further exploration in vivo because some endogenous factors can exert synergistically or antagonistically effect on the binding affinity 63 .…”
Section: Discussionmentioning
confidence: 87%